2021
DOI: 10.1111/1462-2920.15635
|View full text |Cite
|
Sign up to set email alerts
|

Microscopic and biomolecular complementary approaches to characterize bioweathering processes at petroglyph sites from the Negev Desert, Israel

Abstract: Throughout the Negev Desert highlands, thousands of ancient petroglyphs sites are susceptible to deterioration processes that may result in the loss of this unique rock art. Therefore, the overarching goal of the current study was to characterize the composition, diversity and effects of microbial colonization of the rocks to find ways of protecting these unique treasures. The spatial organization of the microbial colonizers and their relationships with the lithic substrate were analysed using scanning electro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 74 publications
(99 reference statements)
2
11
1
Order By: Relevance
“…The microorganism communities associated with rock varnish have been previously studied to determine whether or not there is a connection between the varnish and the microorganisms inhabiting the stone. The results of our metagenomic study are consistent with the findings reported in the literature [25,33], revealing a microbiome dominated by bacteria, with lower proportions of eukaryotes, and archaea representing less than 1% of the total assigned reads. Within the bacteria, Actinobacteria and Cyanobacteria were the most abundant phyla, followed by Proteobacteria and Bacteroidetes, as found also by other authors in metagenomics studies on microbial communities of stones in desert environments [16,27,30].…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…The microorganism communities associated with rock varnish have been previously studied to determine whether or not there is a connection between the varnish and the microorganisms inhabiting the stone. The results of our metagenomic study are consistent with the findings reported in the literature [25,33], revealing a microbiome dominated by bacteria, with lower proportions of eukaryotes, and archaea representing less than 1% of the total assigned reads. Within the bacteria, Actinobacteria and Cyanobacteria were the most abundant phyla, followed by Proteobacteria and Bacteroidetes, as found also by other authors in metagenomics studies on microbial communities of stones in desert environments [16,27,30].…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies mentioned the presence of fungi and lichens, such as Caloplaca sp., as a weathering agent of rock substrates due to the production of oxalic acid and consequent formation of calcium oxalates that can facilitate the disintegration of the calcareous matrix [33]. In this study, however, we could not detect the presence of calcium oxalates.…”
Section: Discussioncontrasting
confidence: 77%
See 3 more Smart Citations